Bioactive Compounds in Moringa oleifera Lam. Leaves Inhibit the Pro-Inflammatory Mediators in Lipopolysaccharide-Induced Human Monocyte-Derived Macrophages - Luetragoon, Thitiya (Molecules, 2020)
Moringa oleifera (MO) is an important plant for traditional medicine. The present study aimed to identify the MO active phytochemical compounds for their ability against inflamed macrophages. An ethyl acetate extract fraction of MO was fractionation by flash column chromatography. Human macrophages were stimulated by Lipopolysaccharide and then treated with fractions of MO to examine their anti-inflammatory activity and cellular mechanism. The active fractions were analyzed by liquid chromatography with electrospray ionization quadrupole time-of-flight mass spectrometer (LC-ESI-QTOF-MS). MO treated cells showed a decreased production of pro-inflammatory mediator in response to lipopolysaccharide. This was evident at both mRNA and protein levels. The study revealed that MO suppressed mRNA expression of IL-1, IL-6, TNF-α, PTGS2, NF-κB (P50), and RelA. Furthermore, the extract effectively inhibited the expression of inflammatory mediators, including IL-6, TNF-α, and cyclooxygenase-2. Interestingly, the effect of MO inhibited phosphorylation of IκB-α and the ability to reduce expression of the nuclear factor (NF)-κB p65, suppressing its nuclear translocation. Moreover, LC-ESI-QTOF-MS analysis of the MO active fraction revealed seven compounds, namely 3,4-Methyleneazelaic acid, (2S)-2-phenylmethoxybutane-1,4-diol, (2R)-2-phenylmethoxybutane-1, 4-diol, γ-Diosphenol, 2,2,4,4-Tetramethyl-6-(1-oxobutyl)-1,3,5-cyclohexanetrione, 3-Hydroxy-β-ionone, and Tuberonic acid. Our findings highlight the ability of MO compounds to inhibit inflammation through regulation of the NF-κB pathway.